Relationship Of Brand Image, Trust and Value on Purchase Intention of Hotels Using Online Technology in China - Hoo, Wong Chee; Guodian, Wu; Wolor, Christian Wiradendi; Ling, Zhu; Prompanyo, Manoch (Journal of Ecohumanism, 2024)
According to a 2015 survey on Chinese outbound tourist consumption, more than a third of Chinese tourists saw travel as equally important as learning and education, career development, child growth, and family wealth. This led to a significant improvement in both the well-being of individuals and their quality of life indicators. When customers have a wider range of options to choose from when making reservations, they are more likely to encounter difficulties in incorporating all of these choices. When customers interact with these forces in the same manner as they do with other forces, conventional variables such as brand image, price, trust, and value will significantly influence their decisions. This means that consumers will interact with these forces in the same manner. We are conducting this study to identify the factors that influence customers' purchase intentions when they make hotel or online reservations in China. The study gathered the information from 392 individuals who responded to the questionnaire. We performed an analysis of the obtained data using SPSS. The conclusion that can be drawn from this is that there is a substantial association between the dependent variable, which is the consumer's desire to make a purchase while booking a hotel online, and three independent factors, namely brand image and trust. On the other hand, we found that the price significantly influences the customer's desire to make a purchase when they book a hotel online. According to the findings of this research, it is possible to draw the conclusion that consumers in China have the same viewpoint and concerns as consumers in other countries when it comes to booking a hotel via an online platform.